Voices from EMU: Student and Instruction Beliefs About National Professional Teaching Standards - Uysal, Merve (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
[Abstract Not Available]
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Assoc. Prof. Dr. Canan Perkan Zeki.
Keywords: English Language Teaching (ELT); English language - Study and teaching (Higher); Professional Teaching Standards; Professional Teaching Standards Framework; Quality Teaching and Teacher Quality